2019
DOI: 10.19044/esj.2019.v15n8p144
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Inequality in Urban and Rural Water, Sanitation and Hygiene Services in Sub-Saharan Africa

Abstract: The attainment of the Sustainable Development Goals (SDGs) for water, sanitation and hygiene (WASH) requires the elimination of all forms of inequalities in WASH services. Hence, this study was aimed at the assessment of the dimensions of inequality in urban and rural WASH services in sub-Saharan Africa. This study adopted a descriptive design based on secondary data obtained from the 2015, Joint Monitoring Programme (JMP) report that contains global estimates on WASH services. The obtained data were presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…This situation calls for radical changes and reforms in the WASH sector to improve on the rates of annual progress on sanitation and hygiene services in all the countries in the region, especially those that at the rock bottom of the progression ladder. Some of the challenges that militate against sanitation and hygiene provisions in the region include poor WASH policy, poor financing, corruption in the WASH sector, poor capacity of governmental agencies in charge of the WASH sector, poverty, political commitment, illiteracy amongst others (Ohwo, 2019;Kumwenda, 2019;Bishoge, 2021). Any developed strategy to scale up sanitation and hygiene provision in the region must address these and other constraints before reasonable progress can be achieved The study established that the rate of progress towards the attainment of SDG 6, target 6.2 in SSA is unsatisfactory, as a large proportion of the population in the region still practices OD and had no hygiene services in 2020.…”
Section: Resultsmentioning
confidence: 99%
“…This situation calls for radical changes and reforms in the WASH sector to improve on the rates of annual progress on sanitation and hygiene services in all the countries in the region, especially those that at the rock bottom of the progression ladder. Some of the challenges that militate against sanitation and hygiene provisions in the region include poor WASH policy, poor financing, corruption in the WASH sector, poor capacity of governmental agencies in charge of the WASH sector, poverty, political commitment, illiteracy amongst others (Ohwo, 2019;Kumwenda, 2019;Bishoge, 2021). Any developed strategy to scale up sanitation and hygiene provision in the region must address these and other constraints before reasonable progress can be achieved The study established that the rate of progress towards the attainment of SDG 6, target 6.2 in SSA is unsatisfactory, as a large proportion of the population in the region still practices OD and had no hygiene services in 2020.…”
Section: Resultsmentioning
confidence: 99%
“…[12,13] The urban-rural disparity in hygiene behaviour has long been established in the literature. [13,30] Other studies reported lower odds of the practice of disposing of child faeces unsafely in urban areas compared with rural areas. [12,13] In contrast, we found higher odds of unsafe disposal of children's faeces in urban areas than in rural areas; this could be explained by the fact that in Eswatini, the majority of households that disposed of child stools in a pit latrine are in rural areas, compared with flush toilets in urban areas.…”
Section: Researchmentioning
confidence: 99%
“…A 100 million Nigerians lack basic sanitation and some 12% of the urban population in also practice open defecation contrary to reports that open defecation has been eradicated in urban areas (Mansor, Islam, and Akhtaruzzaman, 2017). Disparities exist even within rural communities related to household wealth/income (Ohwo, 2019;Ordinioha 2008), level of education (Abubakar, 2017). Solid waste (garbage) disposal has been described as the usual way solid waste or garbage is collected and disposed of by residents of a housing unit (United Nations Statistics Division (UNSD), 2018).…”
Section: Introductionmentioning
confidence: 99%